Ethnomulticultural dimensions in Osing literature of Banyuwangi: An analysis of Samar Wulu and Lintrik - Akhmad Taufiq; Sukatman Sukatman; Budi Setyono (Studies in English Language and Education, 2024)
This study explores the ethnomulticultural content in Osing literature, highlighting how it expresses the Osing ethnic identity through its unique characteristics and traditions. Through a qualitative-interpretative-anthropological method, this study examined data in the form of words, sentences, and paragraphs extracted from two short stories. The short stories under investigation included a short story entitled Samar Wulu (Dusk; the time when the Sun is about to set) by Andika Fitriyah and Lintrik (Love Spell) by Dyah Agustin Wulandari. In this literary anthropology research, the data in the two short stories were analyzed based on their ethnomulticultural content. The ethnomulticultural analysis explored cultural phenomena and traditions, which included worldviews and local wisdom. The researchers conducted a three-stage reading process of the short stories for the representation of Osing cultural content: receptive reading, repeated readings to gather data on ethno-multicultural elements, and interpretive reading using a literary anthropology approach to analyze the worldview and local wisdom of the Osing community. The results revealed the significant role rituals play in expressing Osing cultural identity. Rituals like Kebo-Keboan, for overcoming plagues, and Lintrik, for warding off misfortune, are deeply rooted in Osing society and reflect themes of magic and tragedy. These rituals embody the Osing worldview, where harmony between the micro and macro cosmos is essential. The presence of magical realism in these rituals affirms the local identity of the Osing people in postcolonial society. The findings suggest potential avenues for integrating cultural insights into pedagogical approaches at the junior high school level.